2021
DOI: 10.9734/jpri/2021/v33i38b32099
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Physical Therapy Rehabilitation Program for Women Following a Modified Radical Mastectomy: A Case Report

Abstract: Background: The most commonly identified cancer is breast cancer. In either the lobules or the breast ducts, the cancer normally grows. Infiltrating ductal carcinoma is the most common subtype. It may appear as a lump or mass; changes in the skin or nipple; breast rash or redness; or lymphadenopathy. Presenting Complains and Investigations: the patient presented with the complains of  swelling and pain in the left breast in lower outer quadrant since 6 months, which was initially small in size and gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Early medical rehabilitation on the 2nd-4th day after surgery has been found to help reduce pain syndrome and postoperative edema, enhance shoulder joint motions, prevent severe lymphocytosis, and improve life quality in patients who have had a radical mastectomy (Blomqvist et al, 2004). This event illustrates the need for an early rehabilitation program; early rehabilitation after MRM increases shoulder mobility and functional ability without negatively impacting the postoperative period (Gaur et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early medical rehabilitation on the 2nd-4th day after surgery has been found to help reduce pain syndrome and postoperative edema, enhance shoulder joint motions, prevent severe lymphocytosis, and improve life quality in patients who have had a radical mastectomy (Blomqvist et al, 2004). This event illustrates the need for an early rehabilitation program; early rehabilitation after MRM increases shoulder mobility and functional ability without negatively impacting the postoperative period (Gaur et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It's a type of cancer that starts in the inner layer of the milk ducts or the lobules that feed the ducts with milk. As a result of role constraints caused by physical and emotional problems, young and active patients may find it difficult to return to ordinary daily life activities (Gaur et al, 2021). Breast cancer detection and diagnosis have greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to aware the community about the early signs and symptoms of chronic kidney disease. (13)(14)(15)(16)(17)(18)(19)(20)(21) A scientific study was done in 2018 regarding the relation between chronic kidney disease and cognitive functions and found out that vascular injury can be a major cause of it. The deposition of calcium in the blood vessels makes the blood vessels stiff calcification appears.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acyanotic and cyanotic high-flow lesions, as well as those with pulmonary stenosis, should be treated by doctors with a high index of suspicion for the development of pulmonary tuberculosis. (22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Rana Olguntürk, F.Sedef Tunaoğlu, Levent Gökgöz, Leyla Memiş, and Serdar Kula et al reported after seeing clinical improvement, the patient had surgery. The tricuspid valve underwent ringplasty, and the atrial septal defect was repaired.…”
Section: Discussionmentioning
confidence: 99%